2015
DOI: 10.1039/c5ob00296f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of 1,2-trans alkyl galactofuranoside mimetics as mycobacteriostatic agents

Abstract: The simple octyl β-D-galactofuranoside was previously described as a good bacteriostatic agent against Mycobacterium smegmatis, a non-pathogenic model of M. tuberculosis. In order to decipher its mechanism of action, STD NMR on whole M. smegmatis cells was implemented. It outlined the crucial role of the alkyl chain and the possibility of modulation on the furanosyl entity. Then, 16 new alkyl furanosides were synthesized in order to optimize the mycobacteriostatic activity. They all present the pending alkyl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…However, different innovative and facile approaches have intensively evolved nowadays. [21][22][23][24][25] Previously we developed a method for synthesis of furanoside 9 employing the novel pyranoside-into-furanoside rearrangement. 16 The reported 16 synthesis of donor 9 was started from the β-isomer of fucopyranoside 10, however its preparation is multistep and laborious due to the necessity of difficult chromatographic separations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different innovative and facile approaches have intensively evolved nowadays. [21][22][23][24][25] Previously we developed a method for synthesis of furanoside 9 employing the novel pyranoside-into-furanoside rearrangement. 16 The reported 16 synthesis of donor 9 was started from the β-isomer of fucopyranoside 10, however its preparation is multistep and laborious due to the necessity of difficult chromatographic separations.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ 8.43 (s, 1H, NH), 7.28-7.11 (m, 15H, 3 × Ar), 6.30 (s, 1H, H-1), 4.62 (d, 1H, J = 11.9 Hz, CHH′Ph), 4.49 (m, 3H, CH 2 Ph, CHH′Ph), 4.36 (q, 2H, J = 11.8 Hz, CH 2 Ph), 4.25 (t, J = 5.4 Hz, 1H, H-4), 4.15 (d, J 2,3 = 1.9 Hz, 1H, H-2), 3.96 (dd, J 2,3 = 1.8 Hz, J 3,4 = 5.9 Hz, 1H, H-3), 3.68 (dd, J 4,5 = 5.2 Hz, J 5,6 = 6.3 Hz, 1H, H-5), 1.14 (d, J 5,6 = 6.4 Hz, 3H, H-6). 13 (25). Glycosylation of acceptor 14 (184 mg, 0.43 mmol) with donor 9 (277 mg, 0.47 mmol) as described in the general procedure B gave disaccharides 26: α-isomer (203 mg, 55%), β-isomer (48 mg, 13%).…”
Section: General Procedures B Glycosylationmentioning
confidence: 99%
“…More recent studies have also revealed that 1,2-trans alkyl galactofuranosides also display anti-mycobacterial activity. 12 Previous studies from this laboratory have included the synthesis of a series of glycosyl sulfones 13 and triazoles 14 of arabinofuranose, which were decorated with various hydrophobic side chains. In the former study systematic variation of the alkyl chain length revealed that the C-12 compound was the most active, as demonstrated by an MIC against M. Bovis BCG of 62 µg/mL.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, their syntheses are much more tedious because of the unfavorable competition with the thermodynamically more stable pyranosyl isomers. 9,11,12 An interesting alternative would be to use a specific biocatalyst, able to convert an easy to obtain galactofuranosyl donor into compounds of interest in a single step, simply through reactions with the desired acceptors. This enzymatic strategy would avoid any isomerisation into pyranose and generally lead to a single anomer.…”
Section: -9mentioning
confidence: 99%